Principales causas que limitan la satisfacción del visitante nacional y extranjero a la provincia de San Martín – 2014 - Ushiñahua Garcia, Hussein Sistero (2015)
Tourism is gaining every day more followers, taking advantage of people have more leisure time within which the travel deals and take a leading role. The purpose of this research is to determine the main causes that limit the satisfaction of domestic and foreign visitors arriving in the Province of San Martin. It is to assess the level of satisfaction. Given the hypothesis that the causes that limit the satisfaction of domestic and foreign visitors are: the low quality of tourism services, inadequate information attractions and vehicular disorder. After a review of the scientific literature on the quality of services and their importance in tourist satisfaction. For this we have developed an instrument for consistent measurement in a survey that was administered during the period between the months of September and October 2014 and abroad in the Province of San Martin visitors, whose data have been analyzed using the program SPSS. In the conclusions we can say that a large percentage were foreigners and were satisfied in most of the services used and also designated as the main cause of dissatisfaction to vehicular disorder, but ultimately does not affect the satisfaction of their stay in San Martin, and therefore are willing to recommend visiting this tourist destination